2021
DOI: 10.1186/s12888-021-03396-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of web-based self-management interventions for depressive symptoms: a meta-analysis of randomized controlled trials

Abstract: Background The incidence of depression is increasing worldwide. Depression can lead to poor physical health and even suicide. However, in high-income countries, only about 50% of the people with depression receive appropriate therapy, and the detection rate of depression in low- and middle-income countries is relatively lower. Web-based self-management enables remote treatment and solves the problem of insufficient psychological treatment resources. Many past studies have evaluated the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…Two meta-analyses found that unsupported DMHIs were significantly more effective than supported DMHIs [ 60 , 66 ]. When focusing exclusively on studies of individuals with elevated symptoms of depression [ 6 , 40 , 41 , 43 , 71 ], supported DMHIs were more effective in reducing depressive symptoms than unsupported DMHIs (with 3 studies showing significant findings and 2 failing to find significant differences).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two meta-analyses found that unsupported DMHIs were significantly more effective than supported DMHIs [ 60 , 66 ]. When focusing exclusively on studies of individuals with elevated symptoms of depression [ 6 , 40 , 41 , 43 , 71 ], supported DMHIs were more effective in reducing depressive symptoms than unsupported DMHIs (with 3 studies showing significant findings and 2 failing to find significant differences).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies were rated as low quality, 14 as medium quality, and 1 as high quality based on the AMSTAR 2 quality assessment scale. See Multimedia Appendix 2 [4][5][6][7]38,[40][41][42][43][44][45]47,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] for a list of percentages achieved for each meta-analysis included.…”
Section: Methodological Quality Of the Meta-analysesmentioning
confidence: 99%
See 3 more Smart Citations